CXCL12 is a costimulator for CD4+ T cell activation and proliferation in chronic lymphocytic leukemia patients - Borge, Mercedes (2013)
Activated T cells from patients with chronic lymphocytic leukemia (CLL) provide survival and proliferative signals to the leukemic clone within lymphoid tissues. Recruitment of both, CLL cells and T lymphocytes, to this supportive microenvironment greatly depends on CXCL12 production by stromal and myeloid cells. CXCL12 also supplies survival stimuli to leukemic B cells, but whether it exerts stimulatory effects on T lymphocytes from CLL patients is unknown. In order to evaluate the capacity of CXCL12 to increase CD4+ T cell activation and proliferation in CLL patients, peripheral blood mononuclear cells were cultured with or without recombinant human CXCL12 or autologous nurse-like cells, and then T cell activation was induced by anti-CD3 mAb. CXCL12 increases the proliferation and the expression of CD25, CD69, CD154, and IFNγ on CD3-stimulated CD4+ T cells from CLL patients, similarly in T cells from ZAP-70+ to ZAP-70- patients. Autologous nurse-like cells establish a close contact with CD4+ T cells and increase their activation and proliferation partially through a CXCR4-dependent mechanism. In addition, we found that activated T cells in the presence of CXCL12 enhance the activation and proliferation of the leukemic clone. In conclusion, CXCL12 production by lymphoid tissue microenvironment in CLL patients might play a key dual role on T cell physiology, functioning not only as a chemoattractant but also as a costimulatory factor for activated T cells. © 2012 Springer-Verlag.